When Identity Feels Divided: A Case Report On Gender Dysphoria - Nizami, Asad Tamizuddin; Malik, Ifrah Javed; Mirza, Kainat Kareem; Umar, Zarnain (Journal of Rawalpindi Medical College, 2026)
A psychological condition in which an individual’s feeling of gender is not in congruence with the assigned biological sex is known as gender dysphoria. We shall present the case of a 17-year-old girl who presented with primary amenorrhea to the endocrinology department and was referred to psychiatry. This case report highlights the importance of a multidisciplinary approach.